OPTIMALISASI BAHAN LOKAL UNTUK PENINGKATAN STATUS GIZI: PERAN KEDELAI, TEMPE, DAN DAUN KELOR [MORINGA OLEIFERA] - Susetyowati, Susetyowati; Lestari, Lily Arsanti; Rachmawati, Azizah Isna; Rachmadanty, Ajeng Saskia Sekar; Daud, Zulfitri Azuan Mat; Sholikhati, Amalia Sarah (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2024)
Protein-energy wasting (PEW) is common issue in kidney disease patients, primarily due to inadequate protein and energy intake exacerbated by uremic anorexia. Supplementation of biscuits using local food that contains functional substances have the potential benefit of improving nutrition status in this population. Hence, this experimental study aimed to formulate locally sourced biscuits enriched with high protein, fiber, antioxidants and other nutrients to ameliorate this problem. The study encompassed five key stages: 1) ingredient selection, including soybean (SF) and tempeh flour (TF) as protein, fat, and fiber sources, and Moringa oleifera leaf powder for fiber, vitamins, minerals, and antioxidants; 2) early formulation resulting in three formulation of biscuits namely, SF (45 grams), TF (45 grams), and ST (a combination of 22.5 grams TF and SF), each augmented with 5 grams of Moringa oleifera leaf powder; 3) nutrient analysis on the powder of base ingredients, revealing energy and protein per 100 grams for SF, TF and Moringa oleifera leaf powder were 440 kcal and 34.7 grams, 457 kcal and 39.2 grams, 264 kcal and 23.5 grams, respectively. 4) organoleptic evaluation by trained panelists, leading to the exclusion of SF and TF biscuits due to poor acceptability and unfavorable sensory attributes; and 5) final formulation, where ST biscuits underwent further refinement. In conclusion, ST biscuits show potential as a nutritional intervention for addressing PEW in kidney disease patients, though further research and clinical trials are needed to validate their efficacy and acceptance within this specific patient population.